8 UMP research products won medals in MTE 2021 - Nor Salwana, Mohammad Idris (2021)
PEKAN, 29 October 2021 - Universiti Malaysia Pahang (UMP) continues to shine when eight research products won medals in the online Malaysian Technology Expo or MTE 2021: Sustainable Development Goals International Innovation Award (SDGIIA) recently.